Filtro ativo de potência paralelo utilizando inversores monofásicos full-bridge aplicado em sistemas trifásicos a quatro-fios - Campanhol, Leonardo Bruno Garcia (2012)
This work deals with the study, design and digital implementation by means of digital signal processor (DSP) of a 4.5kVA three-phase shunt active power filter (SAPF), which is implemented by using three single-phase full-bridge converters sharing the same dc-bus voltage. The SAPF is applied to three-phase four-wire systems performing harmonic current suppression, reactive power compensation and load unbalance compensation. The main characteristics of the SAPF topology can be related: possibility of independent current control; low DC-link voltage; galvanic isolation between the SAPF and the grid utility; and possibility of modular implementation. The algorithms adopted for obtaining the current references are based on the synchronous reference frame (SRF) control method. They can be employed in single-phase systems by creating a fictitious three-phase system. Thereby, in a three-phase four-wire system, it is possible the controlling of each phase current independently. Two different operation strategies of the SAPF are implemented. In the first one, which is called Independent Phase-Current Control (IPCC), the SAPF performs harmonic current suppression and reactive power compensation. In this case, the source current will become sinusoidal although unbalanced. In the second strategy, besides acting in the harmonic current suppression and reactive power compensation, the SAPF performs Load Unbalance Compensation (LUnC). In this case, the source currents will become sinusoidal and balanced. Mathematical analyses are carried out in order to obtain the mathematical model which represents the physical system of the SAPF. Additionally, a design methodology is presented, which is used to obtain the controller gains of both current and dc-bus voltage loops. Simulation and experimental results will be presented in order to validate the presented theoretical development and evaluate the performance of the SAPF.